Complementation analysis of measles virus mutants isolated from persistently infected lymphoblastoid cell lines. - Ju, G (1980)
Human lymphoblastoid cell lines persistently infected with measles virus release a heterogeneous population of virions. At least 80% of the infectious particles were temperature sensitive for plaque formation at 39 degrees C. Plaque-purified temperature-sensitive mutants from four persistently infected human lymphoblastoid cell lines were shown to be heterogeneous with respect to efficiency of plating at 31 and 39 degrees C, as well as to antigen and RNA production at 39 degrees C. The heterogeneity was confirmed by complementation analysis in which 21 temperature-sensitive isolates were found to represent at least four of the five previously described complementation groups of measles virus. Two isolates complemented four reference temperature-sensitive mutants. These isolates either represent new complementation groups or are members of the fifth complementation group, group E. The majority of isolates were found to have multiple mutations, and group B mutants (RNA-) predominated. Two temperature-sensitive isolates were able to interfere with production of parental measles virus at both permissive and nonpermissive temperatures.